The 'Viennese epidemic' of acute HCV in the era of direct‐acting antivirals. Issue 5 (15th March 2022) - Chromy, David; Bauer, David J. M.; Simbrunner, Benedikt; Jachs, Matthias; Hartl, Lukas; Schwabl, Philipp; Schwarz, Caroline; Rieger, Armin; Grabmeier‐Pfistershammer, Katharina; Trauner, Michael; Ferenci, Peter; Mandorfer, Mattias; et al.
Abstract: The recently reported epidemic of acute hepatitis C virus (HCV) infections —observed predominantly among men who have sex with men (MSM)—may now decline due to wide availability of direct‐acting antivirals (DAAs). This study aimed to investigate the current trends of acute hepatitis C in Vienna. Patients presenting with acute hepatitis C between 01/2007 and12/2020 at the Vienna General Hospital were retrospectively enrolled and followed after virologic clearance/eradication. The introduction of unrestricted DAA access after 09/17 defined the 'DAA era', as compared to the 'pre‐DAA era' prior to 09/17. We identified 134 acute hepatitis C cases in 119 patients with a mean age of 39 ± 9 years at inclusion. The majority of patients were male (92%), HIV‐positive (88%) and MSM (85%). In the DAA era, a history of prior chronic HCV infection at inclusion was found in 24% (11/46) compared to 7% (5/73) in the pre‐DAA era ( p = .012). The annual rate of acute hepatitis C cases increased in the DAA era (17.11 per year) compared to the pre‐DAA era (7.76 per year). The DAA era included an AHC‐genotype‐2 cluster and more HIV‐negative acute hepatitis C cases (0% (0/73) vs. 30% (14/46), p < .001). Patients were followed after spontaneous clearance or sustained virologic treatment response (SVR) for a total of 251.88 patient‐years (median 1.39 years per patient). In the DAA era, we recorded 15 acute hepatitis C‐reinfections — corresponding to an incidence rate of 5.96 (95% CI: 3.57–9.66) reinfections per 100‐patient‐years. We continue to observe a high incidence of acute hepatitis C in Vienna in the DAA era—primarily among HIV‐positive MSM, but increasingly also in HIV‐negative MSM.